Law of the Sea in Dialogue - Hestermeyer, Holger P. (Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V, 2011)
The interrelation between different fields of public international law has particular relevance for the systematic understanding of international law. The book contains a collection of essays on the law of the sea and its interdependencies with other current legal issues of global importance. The issue of the relationship between global warming and law of the sea matters are one focus. In a second thematic section the collection addresses the global commons. The third part deals with security issues. The recent increase in piracy activities has shown the relevance of discussing the linkage between the law of the sea and security issues.
Includes bibliographical references
Keywords: Konferenzschrift -- 2009 -- Heidelberg; Aufsatzsammlung; Seevölkerrecht